2007
DOI: 10.1002/bit.21755
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent cations and their influence on activated sludge floc chemistry, structure, and physical characteristics

Abstract: Multivalent cations have been known to be important components of activated sludge floc structure due to their bridging ability of the negatively charged sites on the biopolymer network. Recently in batch systems it was found that excess concentration of monovalent cations led to the deterioration in settleability, dewaterability of sludges and effluent quality of the system. In this study, effect of influent monovalent cations (potassium and sodium) on activated sludge floc structure was investigated in semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 39 publications
7
33
0
1
Order By: Relevance
“…The second effect that cations have on biofilm formation is an indirect effect, such that bacteria may respond to changes in concentrations of cations in their surroundings and adjust their metabolism and physiology (8)(9)(10)(11). These bacterial responses may indirectly influence their ability to transition from a planktonic form to an irreversibly attached form and prosper as a biofilm (8)(9)(10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The second effect that cations have on biofilm formation is an indirect effect, such that bacteria may respond to changes in concentrations of cations in their surroundings and adjust their metabolism and physiology (8)(9)(10)(11). These bacterial responses may indirectly influence their ability to transition from a planktonic form to an irreversibly attached form and prosper as a biofilm (8)(9)(10).…”
mentioning
confidence: 99%
“…These bacterial responses may indirectly influence their ability to transition from a planktonic form to an irreversibly attached form and prosper as a biofilm (8)(9)(10). Ca 2ϩ and Mg 2ϩ have been shown to stimulate exopolysaccharide (8,12,13) and extracellular protein (9,14,15) production by bacteria and often have physiological roles in assisting the initial reversible association of bacteria with a surface or enhancing the cohesion of a biofilm (9,11,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, besides the annual cyclic changes, we observed significant differences in the community structures at different SVI levels, as shown in Figs (Fig. S1), suggesting that ion exchange of bivalent cations Ca 2+ and Mg 2+ for monovalent Na + and K + ions (especially Na + ), which could influence sludge aggregation, did not occur (Higgins and Novak 1997;Kara et al 2008;Sobeck and Higgins 2002). Microscopic observations showed that Microthrix parvicella-like filaments were abundant when the SVI value was high (Fig.…”
Section: Discussion Sludge Bulking As the Driving Force For Changes Imentioning
confidence: 53%
“…AS has a negative surface charge, indicated by the negative value of zeta potential (Kara et al 2008). The zeta potential of Stanley AS and Shatin AS was −22.5 and −12.5 mV, respectively.…”
Section: Characteristics Of Asmentioning
confidence: 99%